Bone metabolism, bone mass and structural integrity profile in professional male football players - Filippella, M.; Altieri, B.; Falchetti, A.; Cosso, R. S.; Cena, H.; Musso, C.; Geronutti, E.; Rassat, L.; Cipriani, G.; Colao, A.; Di Somma, C.; Faggiano, A. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Physical exercise plays an important role in bone mineralization as well as factors involved in bone metabolism influence the athletic performance. In European countries, soccer is the most popular sport. The aim of the study was to investigate bone metabolism, bone mass and structural integrity profile in professional male adult football players. METHODS: Sixteen professional male football players from a single team of the Second division Italian League (mean age 22.4±0.7 years) were enrolled. Bone biochemical parameters, including serum calcium, phosphorus, albumin, creatinine, alkaline phosphatase, intact plasma PTH, 25-hydroxy-vitamin D (25-OHD), 24-h urinary calcium and phosphorus, and calcaneal quantitative ultrasound (QUS), were evaluated at the beginning (October 2012) and at the end of the League (May 2013). RESULTS: 25-OHD levels were significantly lower at the end of the League compared to the beginning (27.1±5.9 vs. 36.6±9.5 ng/mL, fold change [FC]=0.25, P=0.008), and the prevalence of 25-OHD deficiency increased from 25% to 73%. Moreover, higher rate of previous bone, cartilage or ligament injuries correlated with 25-OHD deficiencies (P=0.014). T-score and Z-score were at the upper limits of the normality ranges, without significant difference between the beginning and end of the League. Phosphaturia was slightly decreased at the end of the League (691.0±364.5 vs. 934.0±274.3 mg/24h, FC=0.26, P=0.06). A significant correlation was found between phosphaturia and BQI (R2=0.28, P=0.03), and both T-s and Z-s (R2=0.28, P=0.03) at the beginning of the League. CONCLUSIONS: With this pilot study, we demonstrated that vitamin D status significantly worsened at the end of the League. Therefore, vitamin D supplementation might be suggested in adult football players in order to prevent vitamin D deficiency and improve the athletic performance.